Experimental analysis of heat-affected zone HAZ in laser cutting of sugar palm fiber reinforced unsaturated polyester composites - Masoud, Fathi; Salit, Mohd Sapuan; Mohd Ariffin, Mohd Khairol Anuar; Nukman, Y.; Bayraktar, Emin (Multidisciplinary Digital Publishing Institute, 2021)
In this paper, the influence of processing input parameters on the heat-affected zone (HAZ) of three different material thicknesses of sugar palm fiber reinforced unsaturated polyester (SPF-UPE) composites cut with a CO2 laser was investigated. Laser power, traverse speed, and gas pressure were selected as the most influential input parameters on the HAZ to optimize the HAZ response with fixing all of the other input parameters. Taguchi’s method was used to determine the levels of parameters that give the best response to the HAZ. The significance of input parameters was also determined by calculating the max–min variance of the average of the signal-to-noise ratio (S/N) ratio for each parameter. Analysis of variation (ANOVA) was used to determine each input parameter’s contribution to the influence on HAZ depth. The general results show that the minimum levels of laser power and the highest levels of traverse speed and gas pressure gave the optimum response to the HAZ. Gas pressure had the most significant effect on the HAZ, with contribution decreases as the material thickness increased, followed by the traverse speed with contribution increases with the increase in material thickness. Laser power came third, with a minimal contribution to the effect on the HAZ, and it did not show a clear relationship with the change in material thickness. By applying the optimum parameters, the desired HAZ depth could be obtained at relatively low values.